Brain Network Alterations in Rectal Cancer Survivors With Depression Tendency: Evaluation With Multimodal Magnetic Resonance Imaging - Zhang, Wenwen; Zou, Ying; Zhao, Feng; Yang, Yongqing; Mao, Ning; Li, Yuan; Huang, Gang; Yao, Zhijun; Hu, Bin (Frontiers in Neurology, 2022)
Surgery and chemotherapy may increase depression tendency in rectal cancer (RC) patients. Nevertheless, few comprehensive studies are conducted on alterations of brain network induced by depression tendency in RC patients. Resting-state functional magnetic resonance imaging (rs-fMRI) and Diffusion tensor imaging (DTI) data were collected from 42 RC patients with surgery and chemotherapy and 38 healthy controls (HC). Functional network (FN) was constructed from extracting average time courses in brain regions and structural network (SN) was established by deterministic tractography. Graph theoretical analysis was used to calculate network properties. Networks resilient of two networks were assessed. Clinical correlation analysis were explored between altered network parameters and Hamilton depression scale (HAMD) score. This study revealed impaired FN and SN at both local and global levels, changed nodal efficiency and abnormal small-worldness property in RC patients. On the whole, all FN are more robust than SN. Moreover, compared with HC patients, RC patients show less robustness in both networks. Regions with decreased nodal efficiency were associated with HAMD score. These cognitive dysfunctions are mainly attributable to depression related brain functional and structural network alterations. Brain network reorganization is to prevent RC patients from more serious depression after surgery and chemotherapy.